Research on the quick and efficient recovery of 1-allyl-3-methylimidazolium chloride after biomass pretreatment with ionic liquid-aqueous alcohol system. (December 2017) - Liang, Xiaocong; Fu, Yan; Chang, Jie
Graphical abstract: Highlights: No more chemicals introduced to IL systems after IL recovery. Effective recovery of AmimCl after biomass pretreatment. IL recovery ratio reached 93%. IL recovery performance reached 482 g/kw h. Abstract: Membrane-based methodology electrodialysis (ED) was employed for the quick and efficient recovery of ionic liquid AmimCl from the aqueous solutions after biomass pretreatment with AmimCl-aqueous methanol/ethanol systems. IL recovery performance was relatively stable as the variation of IL-alcohol systems employed in the pretreatment process. IL recovery ratio (R) of 66%–71%, IL recovery performance of specific energy consumption (Sp) of 429–467 g/kw h and IL transport rate (Tr) of 5.3–8.2 g/(m 2  min) were obtained by single ED treatment. Enhanced IL recovery performance was resulted with the semi-continuous ED-assisted process with R reached 93% and Sp reached 482 g/kw h. Based on the characteristics of IL solutions, influence of different AmimCl-based solvents pretreatment on IL recovery was discussed and feasibility of electrodialysis treatment for such IL recovery task was also analyzed. Potential gained from this study suggests a feasible methodology for the quick and efficient recovery of ionic liquid after biomass pretreatment.